Peningkatan Ekuitas Merek pada Produk Layanan Transaksi Digital m-BCA: Array - Dien Hawa, Sarah; Syauqi, Achmad (Jurnal Sistem Informasi dan Teknologi Peradaban, 2022)
BCA is one of the banks authorized to issue m-BCA as a digitalize transactions. M-BCA has increased in its transaction and user. M-BCA alwayss be number one Top Brand Index as mobile banking kategory. This study is a survey research that aims to the effect of corporate image, customer sensory experience, brand trust, and perceived value to brand equity. The study was conducted at Indonesia. The sample in this research is 150 m-BCA users as respondents. Sampling technique used is method of accidental sampling method. Data collection techniques methods using questionnaires. The measurement scale uses a Likert scale 7. Data analysis used is analysis using multiple linear regression with the help of SPSS statistics 25. The results showed that: (1) Corporate image have a positive effect on brand equity; (2) customer sensory experience have a positive effect on brand equity; (3) brand trust have a positive effect on brand equity; (4) perceived value have a positive effect on brand equity.